How to ensure no-one uses your theory of change: Lessons from the front lines of theory of change facilitation and possibilities for renewal - and Tangelder, Mary (Theories of Change in Reality, 2024)
This essay discusses how theory of change can be used as a design tool to help funders and their grantees shift from short-term, discrete activities to addressing deeper, systems-level change. Facilitating a theory of change design process as part of an effort to co-design a strategy should, ideally, lead to a strategy that highlights collective efforts and ultimately stimulates meaningful and powerful collaboration. Yet, engaging programme teams and grantees in theory of change has been notoriously difficult, particularly given power dynamics between funders and grantees. Drawing from experience, this essay discusses blind spots and typical stumbling blocks in theory of change design. It builds a case for why we need to rethink and reimagine how to use this tool to inspire action, build shared ownership, drive learning and adaptation, and ultimately accelerate the path to change.